An assessment of the effects of alcohol consumption and prevention policies on traffic fatality rates in the enlarged EU. Time for zero alcohol tolerance?. (October 2017) - Castillo-Manzano, José I.; Castro-Nuño, Mercedes; Fageda, Xavier; López-Valpuesta, Lourdes
Highlights: Effect of alcohol consumption on traffic fatalities is mostly relevant for males. Greater prevalence of alcohol as cause of traffic accidents in Eastern countries. Stricter BAC rate alone does not seem to be a panacea to reduce fatalities. BAC limits below 0.2 g/L are harder to strictly enforce. Higher alcohol prices and legal age for purchase lead to fewer traffic fatalities. Abstract: Some similarities can be seen in the drink driving policies of European Union (EU) countries but there are also some major differences. Although all member States are aware of the need to address the problem, there are considerable differences in aspects such as blood alcohol limits, alcohol prices and the enforcement of alcohol control laws. Considering that these policies are in place in specific economic and cultural contexts, we evaluate the effectiveness of the set of control policies implemented in the EU in terms of traffic fatality rates following the recent enlargement process. For this, we use a panel during the period 1999–2012 controlling for several explanatory economic, demographic and geographical attributes. We find that policies that may be effective for reducing alcohol consumption among young drivers may lead to improvements in road safety. Our results also show that zero approach maximum alcohol concentration rates do not seem to be a panacea for this problem, since the countries with the strictest limits do not achieve better road safety outcomes. Finally, the influence of alcohol consumption on traffic fatalities seems to be particularly relevant for the male population.